Phosphorus based hybrid materials for green fuel generation. Issue 1 (5th October 2022) - Ghosh, Srabanti; Bera, Susmita; Samajdar, Soumita; Pal, Sourabh
Abstract: Phosphorene, also referred to as phosphorus‐based elemental material (black and red), display unusual electronic‐structure characteristics, which can significantly enrich the fields of energy application and possesses huge potential in photocatalysis owing to its bandgap tunability, high optical absorption, large surface area, high charge carrier mobilities, and efficient solar to chemical energy conversion. However, due to chemical instability and the poor visible‐light utilization efficiency, individual phosphorus materials cannot promote charge transfer and separation. For designing active photocatalysts, phosphorus‐based hybrid materials with effective charge carriers separation at the heterojunction interface has played significant role. In this respect, considerable attempts have been made to fabricate black–red phosphorus heterostructure for photocatalytic applications and solar fuel generation, such as photocatalytic and electrocatalysis water splitting, CO2 reduction, carbohydrates synthesis, etc. This review article highlights the strategies for the synthesis of black–red phosphorus heterostructure materials for catalysis with a special focus on their potential for solar fuel generation applications. Recently developed black–red phosphorus heterostructure will be discussed, which can improve the most challenging drawback of phosphorus materials. Finally, the major challenges along with future trends of black–red phosphorus heterostructure in catalytic applications are outlined. This article is categorized under: Sustainable Energy > Solar Energy Emerging Technologies > Materials Emerging Technologies > Hydrogen and Fuel Cells Abstract : Various types of phosphorus based heterostructures, used as photocatalyst for green water splitting, CO2 reduction and N2 fixation under visible light.